Bacteria Pattern, Results of Antibiotic Sensitivity Test, and Complications of Deep Neck Abscess Patients in Dr. Soetomo General Hospital - Syaiful Rijal; Achmad C. Romdhoni (Biomolecular and Health Science Journal, 2018)
Introduction: Deep Neck Abscess is the accumulation of pus inside the potential space between the deep neck fasciae. The incidence has decreased dramatically since the antibiotic era. Empirical antibiotics are administered before the sensitivity test results out, so it is important to know the map of bacteria and its resistance.Methods: This study was conducted retrospectively using medical records of patients with deep neck abscess in Dr. Soetomo General Hospital Surabaya during January 2014-December 2017. Data recorded included gender, age, location, results of bacteria culture examination, antibiotic sensitivity test, and complications that occurred. Data is processed descriptively. Results: Of the 162 patients, 102 (62.96%) were males, followed by 60 females (37.04%). The 46-60 years old group has the largest percentage (33.95%). Whereas the most common location of abscess was in the submandibular (42.59%). Pus culture test, most bacteria is Klebsiella pneumonia (13.04%). While the sensitivity test shows that meropenem has the highest sensitivity number (73.58). Most complications were sepsis, in 48 patients (29.63%). Conclusion: Klebsiella pneumonia, Staphylococcus aureus, and Streptococcus anginosus are the most common etiologies in deep neck abscess. Meropenem, cefoperazone-sulbactam, and oxacillin are the most sensitive antibiotics.